The Rate of Interest in a Dynamic Model - Wright, A. Ll. (Quarterly Journal of Economics, 1958)
I. Introduction, 327. — II. The Hicksian analysis, 328. — III. The integrated model, 332. — IV. The properties of the integrated model, 338. — V. Conclusion, 343. — Mathematical Appendix, 344.